(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The director’s desire to make his picture as true to the tale and place as feasible necessitates the use of architecture to bring out the authenticity as well as realism aspect. This paper is based on Architectural involvement in to theatre and film making process. To understand the important role of architecture, first go through by the glimpse of history of world theatre to Indian Sanskrit theatre. How Indian cinema were origin and presently film making processes involving with architecture, try to present in this paper. The relevance of visual design has been stressed by theatre directors, filmmakers, and animators. Designers have researched the influence of character placements, lighting configurations, and camera movements on transmitting the story, eliciting emotions and moods, and engaging viewers. Many research initiatives concentrated on adjusting the narrative material to the interaction, while the visual presentation received less attention. Authors introduce a novel method to interactive storytelling based on filmmaking theory in this article. The structure is based on principles derived from filmmaking, cinematography, and visual arts theory. Such adaptation, the authors propose, will result in improved engagement and a more interactive story experience.